2013
DOI: 10.1103/physrevd.87.125028
|View full text |Cite
|
Sign up to set email alerts
|

Unitarity in higher-order Lorentz-invariance violating QED

Abstract: The unitarity in Lorentz invariance violating QED consisting of standard fermions and higher-order photons of the Myers-Pospelov theory is studied. We find ghost states associated to the higher-order character of the theory which could render the $S$ matrix nonunitary. An explicit calculation to check perturbative unitarity in the process of electron-positron scattering is performed and it is found to be possible to preserve unitarity.Comment: 7 pages, 2 figures, to appear in Phys. Rev.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…This theoretical framework has inspired a large number of investigations in the last several years, encompassing fermion systems [12][13][14][15][16][17][18][19][20], CPT-probing experiments [21][22][23][24][25][26][27], the electromagnetic CPT-and Lorentzodd term [28]- [41], the CPT-even and Lorentz-odd gauge sector and its interactions with fermions [42][43][44][45][46][47][48][49][50][51], [52][53][54][55][56][57]. Recent investigations involving higher dimensional operators [58][59][60], its possible connections with LV theories [61][62][63][64][65][66], and nonminimal couplings [67][68][69][70]…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical framework has inspired a large number of investigations in the last several years, encompassing fermion systems [12][13][14][15][16][17][18][19][20], CPT-probing experiments [21][22][23][24][25][26][27], the electromagnetic CPT-and Lorentzodd term [28]- [41], the CPT-even and Lorentz-odd gauge sector and its interactions with fermions [42][43][44][45][46][47][48][49][50][51], [52][53][54][55][56][57]. Recent investigations involving higher dimensional operators [58][59][60], its possible connections with LV theories [61][62][63][64][65][66], and nonminimal couplings [67][68][69][70]…”
Section: Introductionmentioning
confidence: 99%
“…We checked that the solution (15) indeed corresponds to a minimum of the effective potential (12). An interesting point to note is that the dynamical mass (15) is analytic in the coupling constant g 2 , unlike the situation of Lifshitz 4-fermion interaction [7,19], where a dynamical mass has the typical non-analytic form…”
Section: Massless Model and Dynamical Mass Generationmentioning
confidence: 92%
“…More general Lorentz-and CPT-violating terms with arbitrary mass dimension have been studied and classified in [9] and [10], in the photon and neutrino sectors, respectively. There are also studies considering perturbative and non-perturbative properties of specific LIV higher order operators, for examples see [11] and [12]. Moreover, some studies regarding Lorentz violation in the neutrino sector whether considering higher order operators or not have been performed, many of them regarding neutrino oscillations, such as [13] and [14].…”
Section: Introductionmentioning
confidence: 99%
“…In quantum field theory, Lee and Wick showed that by imposing the negative norm states to decay it is possible to preserve unitarity order by order in perturbation theory [44,45]. Resurgence of such ideas have been used to solve the hierarchy problem [19,20] and in higher-order effective models with Lorentz symmetry violation [46][47][48].…”
Section: Introductionmentioning
confidence: 99%